(untitled) (Revista Apotheke, 2017)
This paper presents reflections on the design of educational activities in the cartographic perspective in GillesDeleuze e Félix Guattari (1987), and the assumption of a thought through art as experience, based on John Dewey (2010. The educational material serves as a dialog device, an interface between exposure Wanderings About Painting, Educational Action and Aesthetic Experience, in it, the visitor’s of the space gallery, actively contributes to the production of meaning (Rancière, 2014). The authors conceive that there is no a single way of thinking Educational Action and much less a specific way of doing / thinking an educational activity, there are between, hybrid spaces: areas of corporeality, of spatiality, meeting with wealth ambiences, situations and landscapes to be enjoyed and re-created by the spectators. In this sense, the cartographic attitude welcomes the views of the exhibition and recreates new ways of thinking works, providing aesthetic experiences and selfknowledge about artistic productions.